PENGARUH KRIB TERHADAP KECEPATAN ALIRAN PADA SUNGAI KRUENG ACEH - Sari Rezeki; Eldina Fatimah; Masimin Masimin (Prodi Magister Teknik Sipil Unsyiah, 2020)
Krueng Aceh River is one of the rivers that has a large discharge crossing two administrative regions, namely Banda Aceh City and Aceh Besar District. One of the problems in Krueng Aceh river, precisely around the area of Pango fly over towards the downstream area is the high flow speed distribution at the turn of the river. The impact of the bridge pillar on the river turn results in changes in the cross section of the river endangering the public facilities in front of it. Based on this analysis, it is necessary to control and secure the river, namely by placing the Groyne. The purpose of this study is to obtain a speed distribution that occurs from placing Groyne construction. The methodology used in this study with hydrodynamic numerical modeling approach is by using the Surface Water Modeling System program (SMS 11.2). Calibrating with the parameter n = 0.025 has obtained an absolute error value of 0.039 in cross 1 and 0.051 in cross 2. Based on the analysis of 20 scenarios with 7 m and 9 m distance variations, 5-unit and 3-unit Groyne variations, and the variations in perpendicular angle and 10°, 30° (degrees) towards the downstream and the upstream area, as well as the flow speed with the same number of Groyne and distance variations, the result shows that (V7 m V9 m à 5 unit) and (V7 m V9 m à 3 unit). The simulation results show that the more the number of Groyne there are, the more negative the impact on the downstream area becomes, the more narrow the Groyne, the higher the flow speed value increases. From the 20 scenarios, we obtained a Groyne scenario that is in accordance with the field conditions, namely the Groyne scenario with a distance of 7 m, 3-unit cribs, and a Groyne placement angle of 30° towards upstream area (GUb3L7). The result of the velocity distribution observation shows that the scenario of GUb3L7 Existing (without pillars)